The cardioprotective effects and mechanisms of naringenin in myocardial ischemia based on network pharmacology and experiment verification - Yang, Yakun; Qi, Jiaying; Zhang, Muqing; Chen, Pingping; Liu, Yanshuang; Sun, Xiaorun; Chu, Li (Frontiers in Pharmacology, 2022)
Naringenin (Nar) is a natural flavonoid extracted from citrus fruits with abundant pharmacological properties against cardiac diseases, but existing studies are unsystematic and scattered. The present research systematically investigates the mechanism of action of Nar in the treatment of myocardial ischemia (MI). Network pharmacology was used to analyze the relevant targets of Nar against MI as well as the biological mechanisms. The protective effect of Nar was initially assessed in H9c2 cells induced by CoCl2. In acutely isolated rat cardiomyocytes, Nar was further explored for effects on L-type Ca2+ currents, cell contractility and Ca2+ transients by using patch-clamp technique and Ion Optix system. Network pharmacology analysis indicated that Nar improved apoptosis, mitochondrial energy metabolism, inflammation and oxidative stress. Experimental validation demonstrated that Nar decreased ROS and MDA levels and increased antioxidant activity (e.g., GSH-PX, SOD, and CAT), mitochondrial membrane potential, ATP and Ca2+-ATPase contents. Nar also markedly reduced inflammatory factor levels, apoptosis, and intracellular Ca2+ concentrations in H9c2 cells. Based on the experimental results, it is speculated that Ca2+ signals play an essential role in the process of Nar against MI. Thus, we further confirmed that Nar significantly inhibited the L-type Ca2+ currents, contractility and Ca2+ transients in acutely isolated cardiomyocytes. The inhibition of Ca2+ overload by Nar may be a novel cardioprotective mechanism. The present study may serve as a basis for future clinical research, and Nar as a Ca2+ channel inhibitor may provide new perspectives for the treatment of myocardial ischemic diseases.